Plasma BDNF Concentration, Val66Met Genetic Variant, and Depression-Related Personality Traits - Terracciano, Antonio (2010)
Brain derived neurotrophic factor (BDNF) regulates synaptic plasticity and neurogenesis, and BDNF plasma and serum levels have been associated with depression, Alzheimer's disease, and other psychiatric and neurodegenerative disorders. In a relatively large community sample, drawn from the Baltimore Longitudinal Study of Aging (BLSA), we examine whether BDNF plasma concentration is associated with the Val66Met functional polymorphism of the BDNF gene (n = 335) and with depression-related personality traits assessed with the NEO-PI-R (n = 391). Plasma concentration of BDNF was not associated with the Val66Met variant in either men or women. However, in men, but not in women, BDNF plasma level was associated with personality traits linked to depression. Contrary to the notion that low BDNF is associated with negative outcomes, we found lower plasma levels in men who score lower on depression and vulnerability to stress (two facets of Neuroticism) and higher on Conscientiousness and Extraversion. These findings challenge the prevailing hypothesis that lower peripheral levels of BDNF are a marker of depression.